2013
DOI: 10.3348/kjr.2013.14.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Staging of Hepatic Fibrosis: Comparison of Magnetic Resonance Elastography and Shear Wave Elastography in the Same Individuals

Abstract: ObjectiveTo cross-validate liver stiffness (LS) measured on shear wave elastography (SWE) and on magnetic resonance elastography (MRE) in the same individuals.Materials and MethodsWe included 94 liver transplantation (LT) recipients and 114 liver donors who underwent either MRE or SWE before surgery or biopsy. We determined the technical success rates and the incidence of unreliable LS measurements (LSM) of SWE and MRE. Among the 69 patients who underwent both MRE and SWE, the median and coefficient of variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 56 publications
3
62
2
Order By: Relevance
“…18 In contrast, a recent study in overweight patients showed a lower rate of unreliable examinations. Reliable liver stiffness measurements were reported in 96% of patients using the TE-XL probe and 95% using 2d SWE of the right lobe.…”
Section: Vibration Controlled Transient Elastography (Te): Ultrasoundmentioning
confidence: 87%
See 2 more Smart Citations
“…18 In contrast, a recent study in overweight patients showed a lower rate of unreliable examinations. Reliable liver stiffness measurements were reported in 96% of patients using the TE-XL probe and 95% using 2d SWE of the right lobe.…”
Section: Vibration Controlled Transient Elastography (Te): Ultrasoundmentioning
confidence: 87%
“…However, MRE provided significantly more reliable liver stiffness measurements than did SWE shear-wave elastography (100% vs. 86.9%). 18 serum markers prescribe a more superior diagnostic accuracy to radiologic markers. 19 56 In a study comparing serum markers along with TE and 2d SWE, overall non-invasive radiologic markers (TE and SWE) had better performance than non-invasive indirect serum markers of fibrosis such as APRI or FIB-4.…”
Section: A Comparison Of Radiology Markers: In a Study Examining 2d mentioning
confidence: 97%
See 1 more Smart Citation
“…The operator places the region of interest in an area without large vessels, at a depth more than 2 cm, but no further than 8 cm. Until now, there is no consensus regarding the number of measurements that should be performed, three [105], four [106] or five [107][108][109] valid 2D-SWE measurements were performed in different studies. Also, some studies used the mean value of LS measurements [105,106], while in others the median was used [109].…”
Section: Examination Techniquementioning
confidence: 99%
“…An important advantage of this method is complete independence from the operator, and the ability to make measurements in the whole organ, and not a few selected points. The disadvantages include the long duration of the study, the high price of software and difficulties in availability of this method [20,21].…”
Section: Magnetic Resonance Elastographymentioning
confidence: 99%